(untitled) (The Journal of Psychology and Sociology, 2016)
This article presents the results of the application of intra-cultural study of ethnic identity of marginals. Modern Kazakhstan is not a simple connection of different ethnic cultures but represents their complex relationship and interpenetration. In this regard, the intra-cultural study of ethnic identity is one of the most promising ways of theoretical and empirical synthesis – and of particular value to the multicultural Kazakhstan. The object of study: ethnic identity of marginals typical for students of Kazakhstan. Subject of research: intra – cultural characteristics of marginals’ ethnic identity in the conditions of multiethnic state. Methods: for empirical research there was used methodical elaboration «Types of ethnic identity». The reliability of the results was provided by using standard methods of mathematical statistics SPSS Statistics17. The study showed that for the marginals it is characterized by the dominance of positive ethnic identity, which determines the level of standards of ethnic identity (71%). In both samples there is observed relatively high level of ethnic indifference, believing that one’s people are no better and no worse than others (27%). The lowest intensity among students of both samples belonged toethnonihilism – leveling of the ethnic factor (1%) and etnoisolationism (1%), which manifests itself as a form of xenophobia. For the most part of the students of both samplesit ischaracteristi the rate of ethnic identity, that is, the love of his people and at the same time respect to the language and culture of others. The second highest level of intensity belongs to the marginal hypoidentity (27%) and in the control group – hyperidentity (11%). In third place on the intensity degree of the representatives of marginalized groups is hyperidentity, which is characteristic of 2% to 10% of the students in the control group is characteristic hypoidentity. The study also showed that 87% are characterized by low marginal need for ethnic identity, and only 13% by the highest. In the control groupwe received the opposite result: a high need for ethnic identity is characteristic for 83%, and the low demand for – 17% of students.